EFEKTIVITAS BOOKLET TERHADAP PENGETAHUAN DAN SIKAP PEMELIHARAAN KESEHATAN GIGI MULUT PADA IBU HAMIL - Rahmaini Fitri (Jurnal Maternitas Kebidanan, 2019)
Pregnancy causes physiological changes in the body and as well as in the oral cavity. Dental and oral diseases associated with pregnancy that is, gingivitis, periodontitis and pregnancy granuloma. Mouth dental disease during pregnancy is not only influenced by the pregnancy itself but rather the lack of knowledge about dental and oral health maintenance. Efforts to improve the knowledge of pregnant women about oral health is done by providing information, information necessary for health education media. In this case the media is created and used to improve the knowledge of pregnant women is the booklet. This study aimed to analyze the differences in knowledge and attitudes before and after maintenance booklet oral health in pregnant women. This study is a quasi experiment with one group pre and post test design. The sample is the first trimester pregnant women who come to the health center in Sentosa Baru Medan as many as 34 people. Analysis of the data forcompare the average difference in scores of knowledge and attitudes before and after the intervention used the Wilcoxon test. The results showed there is an increased knowledge and attitude maintenance of oral health in pregnant women after being given a booklet with a value of p < 0.001, a percentage increase of 30% knowledge and attitudes percentage of 37%. The conclusions of this study is increased knowledge and attitude maintenance of oral health in pregnant women after being given a booklet.